IMPLEMENTASI PROGRAM KELUARGA HARAPAN DI KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA - LONDAH, ANGGREINI; TAMPI, GUSTAF BUDI; LONDA, VERY (Sam Ratulangi University, 2018)
In the effort to overcome poverty various ways have been done by the government throughSocial assistance programs and One of the programs is the Family Hope Program. The hope familyprogram is a social protection program through the provision of cash assistance to very poor familiesby fulfilling the required requirements related to efforts to improve the quality of human resources,namely education and health. As for the purpose of this research was to determine how theImplementation Of Hope Family Program In Pasan District Southeast Minahasa Regency. Theresearch method used in this study is qualitative research method. Informants in the study are peoplewho can provide information about the situation and condition of the research background. Thefocus of research is communication, resources, disposition and bureaucratic structure. Technique ofcollecting data through observation / direct observation kelokasi research, do interview, anddocumentation. The results showed that the implementation of hope family program in Pasan Districtof South Minahasa Regency has not been implemented well. The lack of socialization to theparticipants of the hope family program and resources in the mentoring process has not been welldone into the implementation of the family hope program appropriately.Keywords : Implementation, Program, Family Hopes